The influence of body mass on gait parameters - Sheehan, Katie (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Physiotherapy, 2012)
This research assessed the relationship between increased body mass and gait. Previous literature has noted that a reduced velocity is adopted by overweight participants. Velocity has been shown to have a confounding influence on gait. It is difficult to determine which changes reported are due to an increase in body mass, and not the result of a reduction in velocity. The author's therefore also assessed the influence of auditory cueing on gait, as a means of constraining velocity. This enabled the direct assessment of the relationship between body mass and gait.
Keywords: Physiotherapy, Ph.D.; Ph.D. Trinity College Dublin